Effect of different cooking water on flavor characteristics of mutton soup. Issue 11 (7th September 2021) - Zhao, Bing; Sun, Baoguo; Wang, Shouwei; Zhang, Yuyu; Zang, Mingwu; Le, Wang; Wang, Hui; Wu, Qianrong
Abstract: The mutton flavor is affected by cooking water significantly, and the flavor of mutton is delicious and widely loved by consumers through an extremely simple processing in northwest China, such as Inner Mongolia, Ningxia, and Xinjiang. The flavor shows obvious changes if get out of these areas even use the same raw meat, which may be caused by different cooking water. To determine whether and how the cooking water affect the mutton soup flavor, the elements in water, the flavor was studied by inductively coupled plasma mass spectrometry (ICP‐MS), amino acid analyzer, and thermal desorption (TDS)–gas chromatography–mass spectrometry (GC‐MS). Specifically, three water samples from different sources, Ningxia (NXW), Beijing (BJW), and ultrapure water from the laboratory (PUW), were used for cooking with Tan sheep's ribs to get different mutton soups. The inductively coupled plasma mass spectrometry (ICP‐MS) results showed that the elements and the concentration of solutes in different water sources were significantly different. The NXW batch had the highest Na, Mg, K, and Sr concentrations, and Na in NXW water reached to 50.60 mg/L, which existed as Na +, significantly ( p  < .05) higher than BJW (8.63 mg/L) and PUW, which were important to the flavor of mutton soup. The PUW batch had the highest content of free amino acids, and the content of glutamic acid (Glu) reached to 17.89 μg/mL. The NXW batch had the highest content of taste nucleotides, and the content of 5´‐IMP reached to 68.68 μg/ml. The volatiles of the three batches had significant differences, and only 40 volatiles were detected in all batches. Further flavor studies using electronic nose and electronic tongue showed significant differences in overall aroma and overall taste, especially bitterness, saltiness, and astringency. The results could provide a basis for improving the flavor quality for the mutton soup. Abstract : In this study, different kinds of cooking water were used in mutton soup preparation to characteristics its effects. The types and concentrations of elements in different types of water showed significant differences. The overall aroma and overall taste had significant differences, especially in bitterness, saltiness, and astringency.